What COVID-19 has introduced into education: challenges Facing Higher Education Institutions (HEIs). Issue 1 (1st January 2021) - Treve, Mark
ABSTRACT: The effect of the latest novel Coronavirus (COVID-19) on higher education, specifically the transition from face-to-face sessions to online and interactive learning systems, is investigated in this study. The paper discusses the difficulties that higher education institutions face in transitioning to 'online pedagogy, ' including mobility issues, technology connectivity, digital learning, and differential access to education. The key obstacles of a shift to distance learning during COVID-19, according to the findings, are technical resources and differential access to education. Though COVID-19 was challenging for students, it also served as a springboard for realistic alternatives such as artificial intelligence (AI), public-private educational collaborations, and digitalization. Universities should study policies to mitigate the detrimental effects of COVID-19, according to the findings, while maintaining a dedication to creativity and large-scale changes in practice.